HUBUNGAN TINGKAT KECEMASAN DENGAN PRODUKSI ASI PERTAMA PADA IBU MELAHIRKAN SPONTAN DI RUANG MAWAR RSUD DR. H. SOEWONDHO KENDAL - Siti Aminah; Yulia Ardiyanti; Eka Listiana; Dwi Haryanti (Jurnal Surya Muda, 2022)
Breast milk or breast milk is a major nutritional source of infants who have not been able to digest solid foods. Breast milk is the best source of food for babies because it has so many important good substances to boost immunity against disease. Condition of postpartum stress experienced 80% of women after delivery. Feeling sad or grumpy that hit the mother arises within two days to two weeks postpartum. The volume of breast milk produced is influenced by the psychological condition of a mother and the food she consumes, therefore the mother should not feel excessive stress and anxiety. This situation is very influential on the volume of breast milk in the first week of breastfeeding the baby. This study aims to determine the relationship of anxiety level with the first breast milk production in spontaneous delivery of mothers in the room Mawar RSUD dr. H. Soewondo Kendal. This research is descriptive correlative, for data collection using questionnaire. The results of the study there is a relationship between the level of anxiety with the first breast milk production in spontaneous delivery with p value 0.000 (p <0.05)